Retarded condensate freezing propagation on superhydrophobic surfaces patterned with micropillars - Zhao, Yugang (2016)
Previous studies have shown ice delay on nano-structured or hierarchical surfaces with nanoscale roughness. Here we report retarded condensate freezing on superhydrophobic silicon substrates fabricated with patterned micropillars of small aspect ratio. We further investigated the pillar size effects on freezing propagation. We found that the velocity of freezing propagation on the surfacepatterned with proper micropillars can be reduced by one order of magnitude, compared to that on the smooth untreated siliconsurface. Additionally, we developed an analytical model to describe the condensate freezing propagation on a structuredsurface with micropillars and the model predictions were compared with our experimental results.